Oral lichen planus with linear lichen planus: a rare association - Padmapriya, N.; Karthikeyan, K. (International Journal of Research in Dermatology, 2019)
Lichen planus (LP) is a papulosquamous disorder with both cutaneous and mucosal manifestation. Linear lichen planus is rare variant of lichen planus which occurs in the extremities. Oral lichen planus is another variant of lichen planus. Coexistence of linear lichen planus with oral lichen planus is rare and only one case has been reported before this case. A 35 year old female presented with hyperpigmented linear lesion in the leg and whitish plaques in the oral cavity. Biopsy of the skin lesions showed features of lichen planus. The patient was started on topical steroids and oral hydroxychloroquine. Patient responded to treatment.